The management of student teachers' learning : a guide for professional tutors in secondary schools - McIntyre, Donald; Hagger, Hazel; Burn, Katharine (London ; Philadelphia : Kogan Page, 1994)
Aimed at professional tutors, this text explains the role of managing student teachers in secondary school settings. It describes how to organize school-based teacher training, how to ensure proper communication between teaching staff and how to measure the effectiveness of mentoring.
Includes bibliographical references.
Keywords: Student teachers -- Supervision of -- Great Britain; High school teachers -- Training of -- Great Britain; Mentoring in education